Thirty years of glacier grounding line retreat in Antarctica - Eric Rignot; Bernd Scheuchl; Jean Baptiste Barre; Virginia Brancato; Laurane Charrier; Hanning Chen; Enrico Ciraci; Andy Dinh; Sam Herreid; Seongsu Jeong; Xin Li; Thomas Mitchell; et al. (Proceedings of the National Academy of Sciences, 2026)
The Grounding Line (GL)—the transition from ice grounded on the continent and ice afloat in the ocean—is a sensitive indicator of glacier stability and mass balance. Using differential synthetic aperture radar interferometry from ERS-1/2, Sentinel-1, RADARSAT-1/2, RADARSAT Constellation Mission, ALOS PALSAR-2, COSMO-SkyMed, and ICEYE, we assemble a continental scale record of grounding line migration from 1992 to 2025. Over 77 ± 10% of Antarctic coastal length, we detect no GL migration. Retreat is concentrated in i) the Antarctic Peninsula–2 to 18 km along Larsen A-B and 2 to 6 km along parts of George VI; ii) Wilkes and George V lands–6 to 10 km on Denman, Totten, Moscow, Frost, Holmes, Mertz, Ninnis, and Cook, and 26 km on Vanderford; and iii) West Antarctica–5 to 7-km on Ferrigno, Fox, and Venable, with extreme retreat in the Amundsen and Getz sectors (Pine Island 33 km, Thwaites 26 km, Haynes 20 km, Pope 23 km, Smith 42 km, Kohler 12 km, East Getz 9 km toward Berry 18 km, Hull 14 km, and Land 5 km). The ice sheet lost 12,820 ± 1,873 km 2 of grounded ice in 1996–2025, or 442 ± 64 km 2 /y, with 62% from West Antarctica and 28% from East Antarctica. Retreat clusters in areas where bathymetry channelizes warm Circumpolar Deep Water toward deep grounding zones where beds are retrograde, except in the northeastern Antarctic Peninsula. The results provide a harmonized benchmark for ice grounding zone-based ice sheet models and identifies gateways where future retreat is likely to accelerate.